MalAware Defensive: A Game to Train Users to Combat Malware - Tyler Moon; Tamirat Abegaz; Bryson Payne; Abi Salimi (Journal of Cybersecurity Education, Research & Practice, 2020)
Several research findings indicate that basic cyber hygiene can potentially deter the majority of cyber threats. One of the ways cybersecurity professionals can prepare users to ensure proper hygiene is to help them develop their ability to spot the difference between normal and abnormal behavior in a computer system. Malware disrupts the normal behavior of a computer system. The lack of appropriate user training has been one of the main reasons behind the exposure of computer systems to threats, from social engineering to viruses, trojans, and ransomware. Basic knowledge about common behavioral characteristics of malware could help users identify potentially abnormal behavior in the systems they use on a daily basis.